Seasonal patterns in the South African share index futures market - G. Watson; E. V.D.M. Smit (South African Journal of Business Management, 1994)
In this article three near futures contracts are examined, namely the All Share Near Future, the All Industrial Near Future and the All Gold Near Future, to determine whether daily futures returns exhibit well-documented seasonal patterns. The detection of seasonal patterns in the daily returns for the three underlying indices, namely the All Share Index, the All Industrial Index and the All Gold Index, is also included. Results are compared to the findings of Hattingh Smit. It is shown that seasonal similarities exist between the futures market and the spot market. Seasonal phenomena in the underlying indices further tend to remain stable over the different sample periods considered.
Keywords: 650